PENGARUH CURRENT RATIO, RETURN ON EQUITY, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM (Pada Perusahaan Konstruksi di Bursa Efek Indonesia Periode 2015-2017) - Fiqih, Bhekti Ainul; Merdiana, Candra Vionela (Universitas Ahmad Dahlan, 2018)
This study aims to determine the effect of Current Ratio (CR), Return On Equity (ROE) and Debt to Equity Ratio (DER) on stock prices. Current Ratio is the liquidity ratio, Return On Equity is the profitability ratio and the Debt to Equity Ratio is the Solvency ratio. The object in this study is a Construction Company listed on the Indonesia Stock Exchange (IDX). The research method in this study is a documentation method with a quantitative approach. The population used amounted to 26 companies, then the determination of the sample was determined through a purposive sampling technique. Based on predetermined2 criteria, a sample of 14 companies was obtained. The results showed that simultaneously the Current Ratio (CR), Return On Equity (ROE) and Debt to Equity Ratio (DER) variables had a significant effect on stock prices. Partially, Current Ratio (CR) has a positive but not significant effect on stock prices, while Return on Equity (ROE) has a positive and significant effect on stock prices and Debt to Equity Ratio (DER) has a negative and significant effect on stock prices. This shows that the company must maintain the value of Return On Equity (ROE) and Debt to Equity Ratio (DER).